MENINGKATKAN PERILAKU POSITIF DALAM BELANJA MELALUI PHYSICAL DESIGN PADA PUSAT PERBELANJAAN - RAMSEY, RIONA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The number of shopping centers and a growing number of them competing to be visited by consumers. These products are sold in many shopping centers have much in common so that other necessary measures so that consumers are interested in visiting. One way to do this is to design a mall or shopping center with a good design. When visiting a mall there is the desire of consumers for so refreshing beauty of the physical design of shopping centers could provide a boost for consumers to visit.